Micro-influence of vacuum block positions on machinability of acrylic using hybrid vacuum clamping system - Nassiruddin, Muhammad Amirul Adli; Ab Wahab, Norfariza; Abdul Razak, Muhamad Harezul; Azizzi, Muhammad Ridzuan; Abu Bakar, Mohd Hadzley; Sasahara, Hiroyuki (Universiti Malaysia Perlis, 2021)
The double-sided vacuum clamper is used in this project to study the engraving and end mill machining output. This paper proposes a mechanical repair solution for clamping which does not leave any trace on the clamped surface and can accommodate tiny workpiece thicknesses. Mass production must rapidly and efficiently locate the workpiece for specific operations. Using vacuum clamp, which can often clamp small, thin parts, to attach and release the workpiece. The hybrid vacuum system capable to support the capacity of machining with two conditions: continuous air pressure and remained air pressure from the compressor. The design of the dual side vacuum block is fully designed with the software SolidWorks, which is analyzed the mechanical properties by using the Static Analysis Simulation. The findings show that the solid vacuum block Delrin led to improved static analysis results. CNC router machine used in the experiments, with a 3 mm diameter to engrave and end milling process to acrylic workpiece. After the experiment, an evaluation has been made on the extent of precision and surface roughness. The most ideal position of the vacuum clamping is side by side with distance due to the nearer clamping force.